Hours and Wages in the Depression: British Engineering, 1926-1938 - Robert A. Hart (Institute for the Study of Labor (IZA), 2000)
On their intensive margins, firms in the British engineering industry adjusted to the severe falls in demand during the 1930s Depression by cutting hours of work. This provided an important means of reducing labour input and marginal labour costs, through movements from overtime to short-time schedules. Nominal wages dropped relatively modestly while real wages continued to rise throughout the trough years of the recession. Empirical work is based on cell data from a panel of 28 local labour markets for the period 1926-38. The data dichotomise between skilled fitters and unskilled labourers and between time-rate and piecerate workers. The findings have interesting implications for Phillips curve and wage curve studies.
Keywords: J31; E24; N34; 330; British engineering; the Great Depression; hours of work; Phillips Curve; wage curve; Kurzarbeit; Reallohn; Konjunktur; Geschichte; Maschinenbau; Phillips-Kurve; Regionale Lohnstruktur; Schätzung; Großbritannien